The Influence of Intellectual Capital On the Firm’s Value with Profitability as Intervening Variable (Empirical Study on Banking Subsector Companies Listed on the Indonesia Stock Exchange (IDX) of the year 2017-2019) - et. al., Rarassatika Ainunnisa, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The purpose of this study was to determine the effect of intellectual capital on firm’s value with profitability as an intervening variable. Intellectual capital is calculated using Pulic's calculation model. The number of samples in this study were 81 financial statements of 27 banking subsector companies listed on the Indonesia Stock Exchange (IDX) of the year 2017-2019. The conclusions obtained from this study include: intellectual capital has a positive effect on profitability; intellectual capital has a positive effect on company value; profitability has a positive effect on firm’s value; and intellectual capital has a positive effect on firm’s value with profitability as an intervening variable.